Anode sheet surface spot cause analysis method
Patent Information
- Application Number
- CN202311796677.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-12-25
AI Technical Summary
[0005]本发明所解决的技术问题在于克服了现有技术中存在的针对有斑点的负极极片无法得知产生原因,提供一种负极极片表面斑点产生原因的分析方法
[0047]本发明的分析方法可以分析负极极片的制备过程中,涂布物料时由于物料的团聚而产生斑点的原因,帮助从本质源头上锁定负极极片表面斑点问题,可针对性处理实际生产应用过程中遇到的问题,顺利找到可靠的解决方案;并且该分析方法具有较高的准确度和较好的重复性。
Smart Images

Figure CN117761031B_ABST
Abstract
Description
Technical Field
[0001] This invention specifically relates to an analytical method for the causes of spot formation on the surface of a negative electrode sheet. Background Technology
[0002] Sodium-ion batteries have broad application prospects in the energy storage field due to their advantages such as abundant sodium resources, low cost, and good safety performance. For sodium-ion batteries, the quality of the negative electrode sheet not only has a significant impact on the production cost of enterprises, but also directly affects the overall dynamic performance of the battery. However, in the existing sodium-ion battery negative electrode sheet manufacturing process, defects such as uneven coating introduced by adjusting coating parameters and particle agglomeration defects introduced by adjusting slurry parameters can lead to defects in the prepared negative electrode sheet, resulting in electrode waste and increased production costs.
[0003] In Chinese patent document CN112014744A, electrode defects are divided into three categories: uneven coating defects, overall uneven coating defects, and particle agglomeration defects. Tests are conducted on electrodes with different defects to screen them. However, the patent document does not provide analysis methods for the defects.
[0004] Therefore, analyzing the causes of defects in defective negative electrode sheets is a problem and a challenge in this field. Summary of the Invention
[0005] The technical problem solved by this invention is to overcome the limitation in existing technologies where the cause of spots on negative electrode sheets cannot be determined, and to provide an analytical method for determining the cause of spots on the surface of negative electrode sheets. This analytical method can determine the cause of spots on negative electrode sheets, helping to solve the problem of spots on electrode surfaces from its root cause, and the analytical method has high accuracy and good repeatability.
[0006] The present invention solves the above-mentioned technical problems through the following technical solutions:
[0007] This invention provides a method for analyzing the causes of spot formation on the surface of a negative electrode sheet, which includes the following steps:
[0008] S1. Obtain the defect degree of the raw materials used to prepare the negative electrode sheet to be tested; wherein, the raw materials are carbon-based active materials and conductive agents;
[0009] S2. Obtain the defect degree of the normal area and the spotted area of the negative electrode sheet to be tested, respectively;
[0010] S3. Based on the results of steps S1 and S2, perform the following analysis:
[0011] If the defect degree of the normal area is greater than the defect degree of the spot area, then the substance that causes the spot formation on the surface of the negative electrode sheet to be tested is determined to be the substance with a smaller defect degree in the raw material, denoted as substance A;
[0012] If the defect degree of the normal area is less than that of the spot area, then the substance that causes the spot formation on the surface of the negative electrode sheet to be tested is determined to be the substance with a larger defect degree in the raw material, and is denoted as substance A.
[0013] If the defect degree of the normal area is equal to the defect degree of the spotted area, then the substance causing the spots on the surface of the negative electrode sheet under test cannot be determined.
[0014] The order of steps S1 and S2 is not limited; the degree of defect is represented by ID / IG.
[0015] In this invention, preferably, the greater the difference in defect levels between the carbon-based active material and the conductive agent, the higher the accuracy of the analytical method in determining the substance causing the spots on the surface of the negative electrode sheet under test.
[0016] In this invention, the negative electrode sheet to be tested can be a conventional negative electrode sheet used in lithium-ion batteries or sodium-ion batteries, for example, a negative electrode sheet for sodium-ion batteries.
[0017] In this invention, according to the conventions of the art, the negative electrode sheet to be tested is generally selected as the sample to be tested, which is a negative electrode sheet with suspected particle agglomeration defects on the surface of the electrode sheet.
[0018] In this invention, according to conventional wisdom, the normal area generally refers to an area with a smooth surface and no particle aggregation. Generally, a normal area can be considered to be one where no spots are observed on the electrode surface with the naked eye.
[0019] In this invention, according to conventional art, the spotted area generally refers to a defective area caused by particle aggregation. Generally, the presence of spots on the electrode surface observed with the naked eye is sufficient to classify it as a spotted area.
[0020] In this invention, the carbon-based active material can be a conventional carbon-based active material used as a negative electrode active material in the art, such as hard carbon, graphite or soft carbon.
[0021] In this invention, the conductive agent can be conventional in the art, such as conductive carbon black SP.
[0022] In this invention, according to conventional practice in the art, the degree of defect can generally be measured by a Raman spectrometer.
[0023] In this invention, the testing process for the degree of defect can be conventional in the art and generally includes the following steps: placing the sample to be tested on the test stage of the Raman spectrometer for testing.
[0024] During the test, observation is usually performed first with a 50x objective lens. The lifting platform is adjusted to project the light spot onto the surface of the sample to be tested, making the sample clear. Then, the objective lens magnification is switched to perform the test.
[0025] When the sample to be tested is a solid particle or powder, it is generally placed on a glass slide, flattened, and then tested. The amount of the solid particle or powder sample can be 25mg-75mg, for example, 50mg.
[0026] When the sample to be tested is a negative electrode sheet, it is generally placed directly on the test bench for testing.
[0027] In testing the degree of defect, the incident light wavelength of the Raman spectrometer is typically 532 nm, with a spectral resolution of 1 cm⁻¹. -1 .
[0028] In this invention, according to conventional art, ID / IG refers to the intensity ratio of the D peak and the G peak.
[0029] In this invention, the defect degree of the carbon-based active material can be 0.938-0.942, for example 0.938, 0.941 or 0.942.
[0030] In this invention, the defect degree of the conductive agent can be 0.870-0.882, for example 0.870, 0.875 or 0.882.
[0031] In this invention, the defect level of the normal area can be 1.037-1.052, for example 1.037, 1.039, 1.041, 1.042, 1.044, 1.045, 1.047, 1.05 or 1.052.
[0032] In this invention, the defect degree of the spotted region can be 1.01-1.018, for example 1.01, 1.012, 1.013, 1.014, 1.015, 1.016, 1.017 or 1.018.
[0033] In this invention, the analytical method preferably includes the following steps:
[0034] In step S1, the particle size of the raw material is obtained, and the substance with a smaller particle size in the raw material is identified and denoted as substance B; in step S3, substance A and substance B are compared:
[0035] If substance A and substance B are the same, then the substance that causes the spots on the surface of the negative electrode sheet is identified as "substance A".
[0036] If substance A and substance B are different, then the substance causing the spots on the surface of the negative electrode is determined, and the conclusion is "suspected to be substance A".
[0037] Through the particle size testing and analysis steps, the results of this invention were further screened, and the reliability of the analytical results of the analytical method was further optimized.
[0038] The particle size generally refers to the particle size D. 50 .
[0039] Wherein, the particle size D of the carbon-based active material 50 It can be 6.0-6.5μm, for example 6.21μm, 6.22μm or 6.24μm.
[0040] Wherein, the particle size D of the conductive agent 50 It can be 2.0-2.5μm, for example 2.26μm or 2.28μm.
[0041] The particle size can generally be measured by a particle size analyzer, such as a Malvern 2000 particle size analyzer.
[0042] The particle size testing process is conventional in the art and generally includes the following steps: diluting the sample to be tested in a solvent to form a suspension for testing. The solvent can be any solvent conventional in the art capable of dispersing the sample to be tested, such as deionized water. The mass percentage of the sample to be tested in the suspension can be 2%-10%, for example, 5%.
[0043] When using a Malvern 2000 particle size analyzer, the particle size testing process may include the following steps: diluting the sample to be tested in a solvent to form a suspension, activating background correction before testing, adding the suspension dropwise to the injector, mixing thoroughly, and then performing the particle size test. Each sample is tested three times, and the average value is taken. Preferably, the suspension is added to the injector while stirring. The stirring speed can be 1500 rpm-2500 rpm, for example, 2000 rpm.
[0044] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0045] The reagents and raw materials used in this invention are all commercially available.
[0046] The positive and progressive effects of this invention are as follows:
[0047] The analytical method of this invention can analyze the cause of spots caused by material agglomeration during the preparation of negative electrode sheets, helping to pinpoint the spot problem on the surface of negative electrode sheets from its root cause. It can address problems encountered in actual production applications and find reliable solutions. Furthermore, this analytical method has high accuracy and good repeatability. Attached Figure Description
[0048] Figure 1 This is a particle size distribution diagram of the hard carbon and SP used in Example 1.
[0049] Figure 2 This is a photograph of the abnormal spots on the negative electrode sheet prepared in Example 1.
[0050] Figure 3 The image shows a Raman image of region 1 of the negative electrode sheet prepared in Example 1. The spherical dark black area is the spot area, and the others are normal areas.
[0051] Figure 4 The image shows a Raman image of region 2 of the negative electrode sheet prepared in Example 1. The black areas are spotted areas, and the others are normal areas.
[0052] Figure 5 This is a photograph of the normal electrode sheet prepared in Example 2. Detailed Implementation
[0053] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0054] Example 1
[0055] (1) The particle size of conductive agent (SP) and hard carbon was tested using a Malvern 2000 particle size analyzer. The main process is as follows: the conductive agent (SP) or hard carbon was diluted with deionized water to prepare a suspension with a mass percentage of 5%. After the background correction of the equipment was turned on, it was used for testing. The prepared suspension was added dropwise to the injector under stirring. The stirring speed was 2000 rpm. After the suspension was added, the ultrasonic treatment was turned on for 3 minutes. Each sample was tested 3 times and the average value was taken to obtain the particle size information of SP and hard carbon.
[0056] (2) The degree of defects of conductive agent (SP) and hard carbon was tested by Raman spectroscopy. The main process is as follows: 50 mg of SP or hard carbon was placed on a glass slide, flattened and placed on the test stage. The 50x objective lens was used for observation. The lifting stage was adjusted to hit the light spot on the sample surface so that the sample was clearly presented. The objective lens magnification was switched for testing to obtain the degree of defects of SP and hard carbon.
[0057] (3) Weigh the materials with a mass ratio of hard carbon:SP:CMC:SBR = 95:1:1.5:2.5, and mix them according to the following process: (This mixing method may create problematic electrode sheets with spotted areas)
[0058] (a) Hard carbon, SP and CMC are all added to a homogenizer for dry mixing. The revolution speed is 35 rpm, the dispersion speed is 0 rpm, and the mixing time is 1 h.
[0059] (b) Add an appropriate amount of deionized water to adjust to a mass fraction of 70%, with a revolution speed of 50 rpm, a dispersion speed of 30 rpm, and a mixing time of 0.5 h;
[0060] (c) Add an appropriate amount of deionized water to adjust to a mass fraction of 65%, with a revolution speed of 50 rpm, a dispersion speed of 30 rpm, and a mixing time of 0.5 h;
[0061] (d) Add an appropriate amount of deionized water to adjust to a mass fraction of 60%, a revolution speed of 70 rpm, a dispersion speed of 30 rpm, and a mixing time of 0.5 h;
[0062] (e) Add an appropriate amount of deionized water to adjust to a mass fraction of 55%, a revolution speed of 70 rpm, a dispersion speed of 30 rpm, and a mixing time of 0.5 h;
[0063] (f) Add an appropriate amount of deionized water to adjust to a mass fraction of 50%, with a revolution speed of 50 rpm, a dispersion speed of 1500 rpm, and a mixing time of 0.5 h. Then keep the revolution speed constant, the dispersion speed at 2500 rpm, and the mixing time at 1.5 h.
[0064] (g) Continue mixing at a revolution speed of 50 rpm, a dispersion speed of 3000 rpm, and a mixing time of 1.5 h;
[0065] (h) Add SBR at a revolution speed of 30 rpm, a dispersion speed of 1500 rpm, and a mixing time of 0.5 h;
[0066] (i) Continue mixing at a revolution speed of 30 rpm, a dispersion speed of 1000 rpm, and a mixing time of 0.5 h. After mixing, the slurry is passed through a 200-mesh sieve and then coated onto the current collector aluminum foil to obtain the negative electrode sheet.
[0067] Note: Vacuum was applied during the stirring process in steps (b) to (i), with a vacuum level of -90 kPa.
[0068] (4) The prepared negative electrode sheet was tested using Raman spectroscopy. The main process is as follows: The prepared negative electrode sheet was placed on the test stage, and observed using a 50x objective lens. The stage was adjusted to project the light spot onto the sample surface, making the sample clear. The objective lens magnification was then switched for testing. The Raman image is shown below. Figure 3 , Figure 4 The test yielded information on the degree of defects in the normal and spotted areas of the negative electrode sheet.
[0069] Example 1
[0070] Figure 1 The particle size distribution diagram is obtained from the first particle size test of raw materials SP and hard carbon, corresponding to the results of the first test in Table 1. From Figure 1 The particle size distribution shows that the conductive agent SP has a wide distribution and a large number of small particles smaller than 1 micrometer. The proportion of particles smaller than 1 micrometer in hard carbon material is relatively small, indicating that SP is more difficult to disperse and more prone to agglomeration.
[0071] Figure 2 These are images of abnormal spots on the negative electrode sheet-1 prepared in Example 1. Figure 2 It can be seen that there are spots on the surface of the prepared negative electrode sheet, thus confirming that the negative electrode sheet belongs to the electrode sheet with spotted areas on the surface.
[0072] Figure 3 and Figure 4 These are Raman images of different regions randomly taken from the negative electrode sheet-1 prepared in Example 1, based on... Figure 3 and Figure 4 It can be seen that there are a large number of abnormal agglomeration areas on the surface of the negative electrode sheet, which presents a spot phenomenon. Raman imaging shows that the abnormal agglomeration areas are black and have a color difference from the normal electrode area. The defect degree data of the normal area and the spot area of the negative electrode sheet are shown in Table 1. The defect degree of the normal area is greater than that of the spot area, and the defect degree of hard carbon is greater than that of SP. It can be concluded that the abnormal agglomerates are mainly contributed by SP.
[0073] Based on the analysis of particle size and defect degree, it can be determined that the substance causing the spots on the surface of the negative electrode sheet-1 is SP.
[0074] Example 2
[0075] To further illustrate the application of this analytical method in analyzing spots on the surface of the negative electrode sheet, the particle size and defect degree of the conductive agent SP and hard carbon in Example 1, as well as the defect degree of the normal area and the spotted area on the prepared negative electrode sheet-1, were each tested three times. The test results are shown in Table 1.
[0076] Table 1
[0077]
[0078]
[0079] As shown in Table 1, according to the analytical method of the present invention, the substance that caused the spots on the surface of the negative electrode sheet was determined to be SP in all three tests, indicating that the analytical method has good stability and repeatability.
[0080] Example 3
[0081] To further illustrate the application of this analytical method in analyzing spots on the surface of the negative electrode sheet, three additional negative electrode sheets with spots were prepared according to the preparation method in Example 1. The degree of defect in the normal area and the spotted area on each negative electrode sheet was tested. Each negative electrode sheet was tested three times. The test results are shown in Table 2.
[0082] Table 2
[0083]
[0084]
[0085] As shown in Table 2, according to the analytical method of the present invention, for each negative electrode sheet, the substance causing the spots on the surface of the negative electrode sheet was determined to be SP in all three tests; for different negative electrode sheets, the substance causing the spots on the surface of the negative electrode sheet was also determined to be SP; indicating that the analytical method has good accuracy and repeatability.
[0086] Example 4: Verification that the substance causing the defect in the negative electrode sheet in Example 1 is SP.
[0087] Weigh the materials with a mass ratio of hard carbon:SP:CMC:SBR = 95:1:1.5:2.5, and mix them according to the following process: 1) Add an appropriate amount of deionized water to CMC to make a 2% solution. The homogenizer rotation speed is 35 rpm, the dispersion speed is 1500 rpm, the mixing time is 4 hours, the vacuum degree is -90 kPa, and the mixture is left to stand for 2 hours; 2) Add SP to the homogenizer, and mix for 20 minutes each at a rotation speed of 35 rpm and dispersion speeds of 1500 / 2000 / 2500 rpm; 3) Add 50% hard carbon, and mix at a rotation speed of... 4) Add an appropriate amount of deionized water and the remaining 50% of hard carbon to make a mass fraction of 55%, and mix at a rotation speed of 50 rpm and a dispersion speed of 2500 rpm for 1 hour; 5) Add an appropriate amount of deionized water to make a mass fraction of 50%, and mix at a rotation speed of 50 rpm and a dispersion speed of 3000 rpm for 2 hours; 6) Add SBR and mix at a rotation speed of 30 rpm and a dispersion speed of 1500 rpm for 0.5 hours; 7) Continue mixing at a rotation speed of 30 rpm and a dispersion speed of 1000 rpm for 0.5 hours. After mixing, the slurry is passed through a 200-mesh sieve and then coated. See the coating photo below. Figure 5 ,according to Figure 5 It can be seen that by specifically adjusting the mixing method of SP to maximize the uniformity of SP mixing, the surface of the negative electrode prepared by this method is normal, and there are no spots caused by agglomeration, which confirms the cause of the defect in Example 1. Note: Vacuum was drawn during the stirring process in steps 2-7, and the vacuum degree was -90Kpa.
Claims
1. A method for analyzing the causes of spot formation on the surface of a negative electrode sheet, characterized in that, It includes the following steps: S1. Obtain the defect degree of the raw materials used to prepare the negative electrode sheet to be tested; wherein, the raw materials are carbon-based active materials and conductive agents; S2. Obtain the defect degree of the normal area and the spotted area of the negative electrode sheet to be tested, respectively; S3. Based on the results of steps S1 and S2, perform the following analysis: If the defect degree of the normal area is greater than the defect degree of the spot area, then the substance that causes the spot formation on the surface of the negative electrode sheet to be tested is determined to be the substance with a smaller defect degree in the raw material, denoted as substance A; If the defect degree of the normal area is less than that of the spot area, then the substance that causes the spot formation on the surface of the negative electrode sheet to be tested is determined to be the substance with a larger defect degree in the raw material, and is denoted as substance A. If the defect degree of the normal area is equal to the defect degree of the spotted area, then the substance causing the spots on the surface of the negative electrode sheet under test cannot be determined. The order of steps S1 and S2 is not limited; the degree of defect is represented by ID / IG.
2. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 1, characterized in that, The negative electrode sheet to be tested is a negative electrode sheet used in lithium-ion batteries or sodium-ion batteries. And / or, the carbon-based active material is hard carbon, graphite, or soft carbon; And / or, the conductive agent is conductive carbon black SP.
3. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 1 or 2, characterized in that, The degree of defect was measured by Raman spectroscopy, and ID / IG refers to the intensity ratio of the D peak and the G peak. And / or, the testing process for the degree of defect includes the following steps: placing the sample to be tested on the test stage of the Raman spectrometer for testing.
4. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 3, characterized in that, When conducting the test, first observe with a 50x objective lens, adjust the lifting platform to project the light spot onto the surface of the sample to be tested so that the sample is clearly visible, and then switch the objective lens magnification to conduct the test. And / or, when the sample to be tested is a solid particle or solid powder, the sample to be tested shall be placed on a glass slide, flattened, and then the test shall be performed. And / or, when the sample to be tested is a negative electrode, the negative electrode is placed directly on the test stage for the test.
5. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 4, characterized in that, The sample amount of the solid particles or the solid powder is 25mg-75mg.
6. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 1 or 2, characterized in that, The defect degree of the carbon-based active material is 0.938-0.942; And / or, the defect degree of the conductive agent is 0.870-0.
882.
7. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 6, characterized in that, The defect degree of the carbon-based active material is 0.938, 0.941, or 0.942; And / or, the defect degree of the conductive agent is 0.870, 0.875 or 0.
882.
8. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 1 or 2, characterized in that, The defect level of the normal area is 1.037-1.052; And / or, the defect degree of the spotted region is 1.01-1.
018.
9. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 8, characterized in that, The defect level of the normal area is 1.037, 1.039, 1.041, 1.042, 1.044, 1.045, 1.047, 1.05, or 1.052; And / or, the defect degree of the spotted region is 1.01, 1.012, 1.013, 1.014, 1.015, 1.016, 1.017 or 1.
018.
10. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 1 or 2, characterized in that, The analytical method includes the following steps: In step S1, the particle size of the raw material is obtained, and the substance with a smaller particle size in the raw material is identified and denoted as substance B; in step S3, substance A and substance B are compared: If substance A and substance B are the same, then the substance that causes the spots on the surface of the negative electrode sheet is identified as "substance A is confirmed". If substance A and substance B are different, then the substance causing the spots on the surface of the negative electrode is determined, and the conclusion is "suspected to be substance A".
11. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 10, characterized in that, The particle size of the carbon-based active material is 6.0-6.5 μm; And / or, the particle size of the conductive agent is 2.0-2.5 μm.
12. The method for analyzing the causes of spot formation on the surface of the negative electrode as described in claim 11, characterized in that, The particle size of the carbon-based active material is 6.21 μm, 6.22 μm, or 6.24 μm; And / or, the particle size of the conductive agent is 2.26 μm or 2.28 μm.
13. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 10, characterized in that, The particle size was measured using a particle size analyzer; And / or, the particle size testing process includes the following steps: diluting the sample to be tested in a solvent to form a suspension for testing.
14. The method for analyzing the causes of spot formation on the surface of the negative electrode sheet as described in claim 13, characterized in that, The solvent is deionized water; And / or, the mass percentage of the sample to be tested in the suspension is 2%-10%.
Citation Information
Patent Citations
Method for evaluating influence of pole piece surface defects on lithium ion battery performance
CN112014744A
Method for evaluating dispersion of conductive agent in lithium ion battery positive electrode sheet
CN108398417A
Composite negative electrode material, preparation method thereof and lithium ion battery
CN115050932A